2005
DOI: 10.1111/j.1467-9582.2005.00118.x
|View full text |Cite
|
Sign up to set email alerts
|

On the locality of left branch extraction and the structure of NP*

Abstract: bstract. The paper considers several accounts of crosslinguistic variation regarding left branch extraction (LBE), focusing on adjectival LBE, and explores consequences of a proper analysis of LBE for the internal structure of NP. Two lines of research are pursued, both of which are based on the claim that languages that allow adjectival LBE do not have DP. One is based on the phase-based locality system, extending the phase system from clauses to NPs, and the other one is based on the existence of crosslingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
257
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(272 citation statements)
references
References 43 publications
4
257
1
4
Order By: Relevance
“…This consequently suggests a bi-phasal architecture of nominal constituents similar to the occurrence of two phasal levels within clauses. Bošković (2008) presents a range of generalizations that distinguish languages with and without articles, and accounts for them by positing a fundamental difference in the structure of nominal projections in language with and without articles, claiming that nominal phrases in languages without articles do not project to any dp layer whereas those with articles do. From among his set of generalizations, we will show that although Bangla does not have articles, it patterns like languages with articles in terms of three generalizations that we discuss below: (a) neg raising, (b) the availability of a majority reading in a language for equivalents to English 'most', and (c) adnominal genitives.…”
Section: (5)mentioning
confidence: 99%
See 2 more Smart Citations
“…This consequently suggests a bi-phasal architecture of nominal constituents similar to the occurrence of two phasal levels within clauses. Bošković (2008) presents a range of generalizations that distinguish languages with and without articles, and accounts for them by positing a fundamental difference in the structure of nominal projections in language with and without articles, claiming that nominal phrases in languages without articles do not project to any dp layer whereas those with articles do. From among his set of generalizations, we will show that although Bangla does not have articles, it patterns like languages with articles in terms of three generalizations that we discuss below: (a) neg raising, (b) the availability of a majority reading in a language for equivalents to English 'most', and (c) adnominal genitives.…”
Section: (5)mentioning
confidence: 99%
“…More recently, in an interesting and influential series of works on this topic, Bošković (2008Bošković ( , 2009) and Bošković and Gajewski (2011) have suggested that languages which do not have (definite) articles are "np languages" and nominal constituents in such languages have no level of dp structure, and that these languages display a number of common syntactic characteristics, which may all be attributed to the absence of d/dp. The present paper approaches this debate with a focus on the potential dp status of (definite) nominal projections in Bangla, a language which has no definite or indefinite articles, but which has special word order alternations in the encoding of definiteness (shortly to be reviewed below) that have been taken to suggest a dp level of structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…sluicing]) correspond precisely to phasecomplements is, from this perspective, very encouraging. 13 One could perhaps even turn the argument around and claim that because NP-ellipsis is well-attested, D ought to be regarded as a phase (as some authors have independently argued; see Svenonius (2004), Bošković (2005), Chomsky (2008), Ott (2008), Samuels (2009), among others). 14 Irurtzun (2007) cites island effects as another context where appeal to labels appears to be necessary, since under most accounts, only certain domains bearing specific labels are opaque (cf.…”
Section: (A)symmetry and Simplicity Considerationsmentioning
confidence: 99%
“…What is crucial for us is that nominals in Polish cannot be bare NPs with modifiers in the adjunct positions (contra Bošković 2005). Whether the nominal projection is actually a DP or any other XP (cf.…”
mentioning
confidence: 99%